The effects of long sprint ability-oriented small-sided games using different ratios of players to pitch area on internal and external load in soccer players - Castagna, C.; D`Ottavio, S.; Cappelli, S.; Araújo Póvoas, S. C. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To examine the internal and external load imposed by long sprint ability-oriented small-sided games (SSG) using different ratios of players to pitch area (densities) in soccer players. Methods: A total of 19 professional soccer players from the same soccer club (age = 17.1 [0.3] y, height = 1.76 [0.69] m, and body mass = 69.7 [9.4] kg) participated in this study. Players performed 4 × 30-s (150 s recovery) all-out 1-vs-1 SSG considering 300, 200, and 100 m2 per player (48 h apart). Players' external loads were tracked with global positioning technology (20 Hz). Heart rate, blood lactate concentration (BLc), and rating of perceived exertion characterized players' internal load. Peak BLc was assessed with a 30-s all-out test on a nonmotorized treadmill (NMT). Results: SSG300 produced higher BLc than SSG200 (moderate) and SSG100 (large). The SSG300, SSG200, and SSG100 BLc were 97.8% (34.8%), trivial; 74.7% (24.9%), moderate; and 43.4% (15.7%), large, of the NMT30s peak BLc, respectively. Players covered more distance at high intensity during the SSG300 than in other SSG conditions (huge to very large differences). High-intensity deceleration distance was largely lower in SSG200 than in SSG300. SSG100 elicited very large to huge and large to very large lower external load values than SSG300 and SSG200, respectively. Conclusions: The main finding of this study showed an inverse association between ball-drill density and internal/external loads in long sprint ability-oriented SSG. The SSG300 provided BLc closer to individual maximal, thus satisfying the all-out construct assumed for the development of long sprint ability. Further studies using the SSG300 as a training intervention and/or investigating other different SSG formats using the same density are warranted.